Cell surface receptor kinase FERONIA linked to nutrient sensor TORC signaling controls root hair growth at low temperature linked to low nitrate in Arabidopsis thaliana. Issue 1 (30th January 2023) - Pacheco, Javier Martínez; Song, Limei; Kuběnová, Lenka; Ovečka, Miroslav; Berdion Gabarain, Victoria; Peralta, Juan Manuel; Lehuedé, Tomás Urzúa; Ibeas, Miguel Angel; Ricardi, Martiniano M.; Zhu, Sirui; Shen, Yanan; Schepetilnikov, Mikhail; et al.
Summary: Root hairs (RH) are excellent model systems for studying cell size and polarity since they elongate several hundred‐fold their original size. Their tip growth is determined both by intrinsic and environmental signals. Although nutrient availability and temperature are key factors for a sustained plant growth, the molecular mechanisms underlying their sensing and downstream signaling pathways remain unclear. We use genetics to address the roles of the cell surface receptor kinase FERONIA (FER) and the nutrient sensing TOR Complex 1 (TORC) in RH growth. We identified that low temperature (10°C) triggers a strong RH elongation response in Arabidopsis thaliana involving FER and TORC. We found that FER is required to perceive limited nutrient availability caused by low temperature. FERONIA interacts with and activates TORC‐downstream components to trigger RH growth. In addition, the small GTPase Rho of plants 2 (ROP2) is also involved in this RH growth response linking FER and TOR. We also found that limited nitrogen nutrient availability can mimic the RH growth response at 10°C in a NRT1.1‐dependent manner. These results uncover a molecular mechanism by which a central hub composed by FER‐ROP2‐TORC is involved in the control of RH elongation under low temperature and nitrogen deficiency.